ICT in the real world a case study in problem solving - Video Education Australasia (Australia : Video Education Australasia, 2010)
Maintaining and developing new and existing technologies requires the use of solid problem solving techniques. This program explain the system of problem solving methodologies that have been devised to assist people in creating technological solutions
Executive producer, Simon Garner ; director of photography, Ben Milward Bason, Jared Marshall
Voice over: Ben McKenzie
DVD format
Keywords: Information technology